Impacts of permafrost on above- and belowground biomass on the northern Qinghai-Tibetan Plateau - Cuicui Mu; Lili Li; Feng Zhang; Yuxing Li; Xiongxin Xiao; Qian Zhao; Tingjun Zhang (Arctic, Antarctic, and Alpine Research, 2018)
Because permafrost is extremely sensitive to climate change, it is of great importance to understand the relationship between permafrost and vegetation biomass. This study aims to reveal the impacts of permafrost on above- and belowground vegetation biomass on the northern Qinghai-Tibetan Plateau. Soil temperature, moisture, active-layer thickness, vegetation coverage, aboveground biomass (AGB), belowground biomass (BGB), and soil organic carbon were investigated in the growing seasons during 2014–2016. The average AGB and BGB in the growing seasons were 0.036 and 0.83 g cm−2, respectively. The AGB was significantly positively correlated with BGB, soil moisture, and soil organic carbon content, but was significantly negatively correlated with mean annual ground temperature and active-layer thickness, suggesting that permafrost degradation can potentially decrease vegetation growth. The BGB was positively correlated with active-layer thickness and was negatively correlated with soil moisture. This study suggests that permafrost degradation can decrease the soil moisture on the northern Qinghai-Tibetan Plateau and thus decrease AGB. The decreased soil moisture can also lead to lower BGB, while the vegetation in drier soils tends to have higher BGB to access more water resources for plant growth.